Month-end regularities in the overnight bank funding markets - Ahmed S. Baig; Drew B. Winters (Journal of Risk and Financial Management, 2021)
The money market rates in the United States exhibit various calendar patterns that are grounded in institutional and regulatory factors. In this paper, we document a new regularity in the overnight fed funds market. Specifically, we identify patterns of decreased volatility along with consistent and significant month-end rate drops in the fed fund rates. Our findings suggest that short-term liquidity requirements of the Basel III reforms are, in part, responsible for the regularity in fed funds.
Keywords: G10; G21; G23; G28; 330; Basel; calendar regularities; federal funds; month-end effect